Pengaruh Karakteristik Pekerjaan Dan Kepuasan Kerja Terhadap Komitmen Organisasional Pada Credit Union Mura Kopa Balai Karangan - B31112004, Aventus Petrus Suparman (Jurnal Manajemen Update, 2017)
Organizational commitment is as a situation where an employee favoring a particular organization and its goals and desires to retain membership in the organization. Organizational commitment owned by employees is an activity that is important to measure the success of an organization in achieving the vision and mission of an organization's. Organizational commitment of the employees themselves, one of which can be influenced by factors characteristic of a job where he had to work and job satisfaction which is owned by the employees themselves. This study aims to examine and analyze the influence of job characteristics and job satisfaction, organizational commitment for at Credit Union Mura Kopa Authorship Hall. Data collected through questionnaires and conducted on 69 people Credit Union employees Mura Kopa Authorship Hall. Analysis of the data in this study using a support program IBM SPSS version 16. The sampling technique used by the census methods and testing techniques of data used in this study include the validity and reliability test. Classical assumption test and multiple regression analysis, to test and prove the hypothesis of the study. The analysis showed that the job characteristics influence positively and significantly related to organizational commitment. Job satisfaction positive and significant effect on organizational commitmentÂ  Keywords: Job Characteristics, Job Satisfaction, Organizational Commitment.